Cegah Dermatitis Dengan Peningkatan Personal Hygiene Melalui Pendekatan Lomba Cuci Tangan Dan Membuat Deterjen Non Alkohol - Milanisti, Anggi Yanda Putri; Br Sijabat, Dischanita; Kharisma M, Gina; Sari, Sandri Fatika; Wulandari, Wulandari; Rohani, Tuti (Utami Publisher, 2024)
There are 10 important programs in Clean and Healthy Living Behavior (PHBS) which are carried out and provided to the community, one of which is washing hands or keeping hands clean (hand hygiene), hand hygiene (hand hygiene) is a way to improve individual personal hygiene in preventing dermatitis and educate children about the habit of washing their hands before or after activities with soap or the like. The use of non-alcoholic detergent is effective in preventing skin irritation which can cause dermatitis, considering that detergent can also be used for household activities such as washing clothes, so using this detergent is considered more economical. The aim of this community service activity carried out in the Batu Urip sub-district, RT 02 Lubuklinggau City, is to provide education to the public about dermatitis, including ways to prevent and avoid this disease with a healthy lifestyle, so that they can maintain a good quality of life. Education is carried out verbally and non-verbally by means of hand washing competitions to increase the habit of washing hands with soap among children aged 7 to 12 years to increase the level of clean living behavior. As well as making your own detergent at home for household activities so that its use becomes more economical. The results of the research showed that hand washing competitions increase clean and healthy living behavior so they are very effective in educating children about the habit of washing their hands before or after activities. As well as increasing and making non-alcoholic detergents, it also increases economic activities among mothers in household activities so that spending on buying detergents becomes more economical. And what's more, non-alcoholic detergent can also be used to wash hands because it doesn't cause irritation to the skin.